REKONSTRUKSI KURIKULUM CINTA BERBASIS MODERASI BERAGAM DI MTs AZHARUL ULUM 02 PADA ERA DIGITAL 2026 - Abd Sakur; Abd Khobir; Moch Umar Faroq Al Farizi; Sita Acetylena (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study aims to reconstruct a Love-Based Curriculum integrated with religious moderation values at MTs Azharul Ulum 02 as a response to moral degradation challenges among students in the digital era of 2026. The curriculum emphasizes the integration of compassion (rahmah), empathy, and religious moderation into all aspects of the madrasah learning process. This research employs a qualitative descriptive approach based on literature review and analysis of madrasah education policies. The findings indicate that the Love-Based Curriculum can be effectively implemented through intracurricular integration, the Project for Strengthening Pancasila Student Profiles and Rahmatan lil ‘Alamin Student Profiles (P5-PPRA), and the development of madrasah culture (hidden curriculum). The implementation of this curriculum contributes to improving students’ psychological well-being, reducing social conflicts, and strengthening moderate and humanistic character development.